Behavioral issues in decision problems: the role of information - VENTRE, Viviana (Journal of Mathematical Economics and Finance, 2018)
Operational research (OR) might exhibit a partial perspective in modelling decisional processes as rational processes, because individual choices are strictly influenced by cognitive and motivational biases which can be different among people and for each person in dierent situation. We point out that the level of information of each problem solver play an important role in causing inconsistent preferences, and we demonstrate that only about strict conditions decision models coincide with real choices, because only in particular cases the optimum and rational decision matches with the real one. Moreover, cognitive and motivational biases influence also the modeler in the process of modelling. Behavioral Operational Research (BOR) studies the influence of behavioral issues in the modelling process, to avoid such kinds of biases and create eficient models to define choices in similar decision processes.